Improving residential environments: analyzing factors influencing individual travel and neighborhood environment - Youngin Song; Seok Lee; Gunwon Lee (Journal of Asian Architecture and Building Engineering, 2025)
Innovation cities have been developed to address regional disparities through the relocation of public institutions to provincial areas; however, insufficient urban infrastructure has hindered population settlement. This study quantitatively analyzed daily travel patterns in smaller urban areas lacking industrial and residential foundations. It aimed to examine the influence of neighborhood environments on travel behavior and propose strategies for enhancing residential sustainability. Commuting trips were analyzed by investigating travel to workplaces or schools, whereas leisure trips were assessed based on travel distance and duration for activities such as recreation. A multiple regression analysis was conducted to evaluate the effects of individual, household, and land-use characteristics on travel behavior. The findings indicated that variables such as occupation, travel area, mode of transport, and total commercial floor area significantly influenced both commuting and leisure trips. Factors specific to commuting included possession of a driver’s license, workplace location, presence of school-aged children, and housing type, whereas gender and housing type influenced leisure trips. This study is significant for empirically demonstrating how neighborhood environments shape travel patterns based on trip purpose. Its results offer a framework for fostering interregional linkages, promoting collaboration, and addressing urban challenges affecting the sustainability and competitiveness of provincial cities.